The threefold protrusions of adeno-associated virus type 8 are involved in cell surface targeting as well as postattachment processing - Raupp, Christina; Müller, Oliver J. (Journal of virology, 2012)
Adeno-associated virus (AAV) has attracted considerable interest as a vector for gene therapy owing its lack of pathogenicity and the wealth of available serotypes with distinct tissue tropisms. One of the most promising isolates for vector development, based on its superior gene transfer efficiency to the liver in small animals compared to AAV type 2 (AAV2), is AAV8. Comparison of the in vivo gene transduction of rAAV2 and rAAV8 in mice showed that single amino acid exchanges in the 3-fold protrusions of AAV8 in the surface loops comprised of residues 581 to 584 and 589 to 592 to the corresponding amino acids of AAV2 and vice versa had a strong influence on transduction efficiency and tissue tropism. Surprisingly, not only did conversion of AAV8 to AAV2 cap sequences increase the transduction efficiency and change tissue tropism but so did the reciprocal conversion of AAV2 to AAV8. Insertion of new peptide motifs at position 590 in AAV8 also enabled retargeting of AAV8 capsids to specific tissues, suggesting that these sequences can interact with receptors on the cell surface. However, a neutralizing monoclonal antibody that binds to amino acids 588QQNTA592 of AAV8 does not prevent cell binding and virus uptake, indicating that this region is not necessary for receptor binding but rather that the antibody interferes with an essential step of postattachment processing in which the 3-fold protrusion is also involved. This study supports a multifunctional role of the 3-fold region of AAV capsids in the infection process.